Antitumor Activity and Antioxidant Status of Caesalpinia bonducella Against Ehrlich Ascites Carcinoma in Swiss Albino Mice - Malaya Gupta; Upal Kanti Mazumder; Ramanathan Sambath Kumar; Thangavel Sivakumar; Madgula Lakshmi Mohan Vamsi (Elsevier, 2004)
The methanol extract of Caesalpinia bonducella FLEMING (Caesalpiniaceae) leaves (MECB) were evaluated for antitumor activity against Ehrlich ascites carcinoma (EAC)-bearing Swiss albino mice. The extract was administered at the doses of 50, 100, and 200 mg/kg body weight per day for 14 days after 24 h of tumor inoculation. After the last dose and 18 h fasting, the mice were sacrificed. The present study deals with the effect of MECB on the growth of transplantable murine tumor, life span of EAC-bearing hosts, hematological profile, and biochemical parameters such as lipid peroxidation (LPO), glutathione content (GSH), superoxide dismutase (SOD), and catalase (CAT) activities. MECB caused significant (P<0.01) decrease in tumor volume, packed cell volume, and viable cell count; and it prolonged the life span of EAC-tumor bearing mice. Hematological profile converted to more or less normal levels in extract-treated mice. MECB significantly (P<0.05) decreased the levels of lipid peroxidation and significantly (P<0.05) increased the levels of GSH, SOD, and CAT. The MECB was found to be devoid of conspicuous short-term toxicity in the mice when administered daily (i.p.) for 14 days at the doses of 50, 100, 200, and 300 mg/kg. The treated mice showed conspicuous toxic symptoms only at 300 mg/kg. The results indicate that MECB exhibited significant antitumor and antioxidant activity in EAC-bearing mice. Keywords:: Caesalpinia bonducella, Ehrlich ascites carcinoma, hematological parameter, antioxidant, antitumor activity